THU0293 The trajectory of radiographic progression slows amongst patients with psoriatic arthritis treated with anti-tnf. (12th June 2018) - Allard, A.; Antony, A.; Shaddick, G.; Jadon, D.; Cavill, C.; Korendowych, E.; McHugh, N.; Tillett, W.
Abstract : Background: Radiographic damage is an important outcome in psoriatic arthritis (PsA) but the natural history of radiographic progression has not been well described. Randomised Controlled Trials (RCTs) of treatment with anti-TNF have shown reduced damage progression in the short term but long term real world data is lacking. Objectives: We set out to describe the long term radiographic progression amongst patients with PsA who transitioned from conventional synthetic Disease Modifying Drugs (csDMARDs) to anti-Tumour Necrosis Factor alpha inhibitors (anti-TNF) in routine care. Methods: A retrospective sample of 28 patients (CASPAR criteria for PsA) was taken from the Bath longitudinal cohort. All patients had radiographs of the hands and feet taken at approximately 3 time points; 5 years before [T0 ], at the time of [T1 ] and 5 years post [T2 ] commencing anti-TNF treatment. 84 radiographs were scored using the Sharp-van der Heijde modified method (VDH) and osteoproliferation was scored using the psoriatic arthritis Ratingen score (PARS) method, by three assessors (AA, AA and WT). The assessors were blinded to the patient details and the order of the x-rays. Inter- and intra-rater reliability was assessed using intra-class correlation coefficients (ICC). Cumulative probability plots were used to describe radiographic progression on csDMARDs (T0 to T1 ) compared with subsequent anti-TNF treatment (T1 to T2 ). Change between probability plots was determined using the two-sample Kolmogorov-Smirnov test (K-S test). This sample size was calculated to ensure 90% power to determine the smallest detectable difference of the VDH (6.25) to 5% significance level. Results: Of the 28 patients 15 were male, the mean age was 61 years (SD 13.4) and mean disease duration at T0 was 11.2 years (SD 11.14). The mean study follow up period was 10.2 years (SD 2.76). Inter- and intra-rater reliability was >0.9. The median VDH score at baseline was 8.5 (IQR 1.75–27.5). The median scores for erosions, joint space narrowing and proliferation at baseline were 1.5 (IQR 0–8.5), 4.5 (IQR 1–15) and 7 (SD1–13.5) respectively. The median change in VDH score on csDMARDs was 11.00 (IQR 3–19.5) and on anti-TNF was 4.00 (IQR 0.75–11.5). The median rate of change in VDH score per year was 2.29 (IQR 0.95–3.81) on csDMARDs and on anti-TNF was 1.04 (IQR 0.16) p=0.012 (figure 1). These scores correlate with observed improvements in clinical disease outcome measures including tender joint count, swollen joint count and nail score (data not shown). Conclusions: In this real world observational cohort study the rate of radiographic progression slows following commencement of anti-TNF therapy. The overall rate of damage progression was low over long term follow up of more than ten years even amongst this group of more severe patients selected on the basis they progressed to anti-TNF therapy. Disclosure of Interest: None declared